1991
DOI: 10.1159/000457505
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Diazepam, Salicylic Acid and Digitoxin to Albumin Isolated from Fetal and Adult Serum

Abstract: Albumin was isolated from pooled fetal serum obtained at normal delivery at term and from pooled adult plasma. Albumin isolation was carried out by means of PEG precipitation followed by ion exchange chromatography on DEAE-Sephadex A 50 and then on SP-Sephadex C 50. The binding of diazepam (1 μM), salicylic acid (2 mM) and digitoxin (6 nM) to albumin (40 g/l) was measured by equilibrium dialysis at 37°C. The unbound fraction (mean ± SD) for fetal and adult albumin of diazepam was 1.86 ± 0.24 and 1.82 ± 0.15% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…One of the concerns is the potential drug-drug interactions that can alter the pharmacokinetics of either ISIS 2302 or concomitant medications. The effective concentrations of each drug evaluated in the interaction experiments were based on published data (Lewis et al, 1971;Cramer and Mattson, 1979;Frey and Frey, 1990;Goodman and Gilman, 1990;Panjehshahin et al, 1991;Viani et al, 1991;He and Carter, 1992;Aki and Yamamoto, 1994;Davies, 1998;Dockal et al, 1999;Fitzpatrick and O'Kennedy, 2004;Trynda-Lemiesz, 2004). Seven drugs with known protein-binding profiles were chosen to investigate the possibility of drug interactions with ISIS 2302 and to help identify a possible binding site for ISIS 2302.…”
Section: Drug Interaction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the concerns is the potential drug-drug interactions that can alter the pharmacokinetics of either ISIS 2302 or concomitant medications. The effective concentrations of each drug evaluated in the interaction experiments were based on published data (Lewis et al, 1971;Cramer and Mattson, 1979;Frey and Frey, 1990;Goodman and Gilman, 1990;Panjehshahin et al, 1991;Viani et al, 1991;He and Carter, 1992;Aki and Yamamoto, 1994;Davies, 1998;Dockal et al, 1999;Fitzpatrick and O'Kennedy, 2004;Trynda-Lemiesz, 2004). Seven drugs with known protein-binding profiles were chosen to investigate the possibility of drug interactions with ISIS 2302 and to help identify a possible binding site for ISIS 2302.…”
Section: Drug Interaction Studiesmentioning
confidence: 99%
“…Drug interaction studies were performed with ISIS 2302 and seven concomitant drugs (warfarin, salicyclic acid, valproic acid, tolbutamide, acetylsalicyclic acid, ibuprofen, and prednisone). These seven drugs were selected on their known binding to albumin or were common drugs used in the treatment of inflammatory disease (or both) (Lewis et al, 1971;Cramer and Mattson, 1979;Frey and Frey, 1990;Goodman and Gilman, 1990;Panjehshahin et al, 1991;Viani et al, 1991;He and Carter, 1992;Aki and Yamamoto, 1994;Rowland and Tozer, 1995;Davies, 1998;Dockal et al, 1999;Fitzpatrick and O'Kennedy, 2004;TryndaLemiesz, 2004). An in-depth knowledge and application of the plasma protein-binding characteristics of PS ODNs are required for the rational application of medicinal chemistry approaches to further modify PS ODNs designed to alter pharmacokinetics or reduce toxicities of ODNs (Henry et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid, a drug available without prescription, is the strongest displacer of furosemide. This drug is used in pregnancy, and the binding of sali cylic acid is dependent on the albumin con centration [10]. In midgestation, fetal albu min concentrations are much lower com pared to those at birth [11], thus the displac ing effect of this drug may be even stronger than at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Furosemide [9] and diazepam, salicylic acid and digitoxin [10] bind to a similar extent to equimolar solutions of newborn and adult albumin, thus suggesting that newborn and adult albumin have similar intrinsic binding properties. The role of hypoalbuminemia in the decreased binding of furosemide in newborn plasma was unknown.…”
Section: Introductionmentioning
confidence: 94%
“…In a study dated 1973 [36], albumin was reported to be present in similar levels in neonates and adults. Although Viani et al [39] found that fetal and adult albumin had similar binding properties, as far as the binding of diazepam, salicylic acid and digitoxin were concerned, they also reported that a number of drugs had significantly higher displacing effects on the binding of furosemide to fetal than to adult albumin [40]. Although Viani et al [39] found that fetal and adult albumin had similar binding properties, as far as the binding of diazepam, salicylic acid and digitoxin were concerned, they also reported that a number of drugs had significantly higher displacing effects on the binding of furosemide to fetal than to adult albumin [40].…”
Section: Plasma Protein Bindingmentioning
confidence: 98%